A study in relationship between absenteeism and jobs satisfaction among employees, UiTM Shah Alam [electronic resource] - Azfar Azmi, 1988-; Ishak Mad Shah, supervisor; Fakulti Pengurusan (2015)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2015